A Critical Evaluation Revealed the Proto-indica Model Rests on a Weaker Foundation and Has a Minimal Bearing on Rice Domestication. (3rd November 2020) - Ray, Avik; Chakraborty, Debarati; Ghosh, Surajit
We have evaluated the proto-indica model that is the proponent of multiple domestication of rice but a single origin of the key genes in japonica . Attainment of non-shattering, a marker; appeared least integral to the initial phases of domestication. The other archeological determinants were less discernible in specimens. Existence of the key domestication genes in the wild rice and absence of introgression signature in indica further weakened the hypothesis. Moreover, japonica introduction from China happened in a backdrop of a culture exploiting domesticated rice. Summarizing, we propose that proto-indica model has a little bearing on rice domestication.